PERSEPSI PETANI TERHADAP USAHATANI SORGUM DI DESA WUAKERONG KECAMATAN NAGAWUTUNG KABUPATEN LEMBATA - Theresia Gelu; Maximilian M. J. Kapa; Selfius P. N. Nainiti (Buletin Ilmiah Impas, 2021)
This research was conducted in the village of Wuakerong Nagawutung District Lembata in January 2020 to February 2020. This research aims to determine (1) the characteristics of farming sorghum, (2) the perception of farmers in sorghum farming, and (3) the obstacles faced by farmers in farming Sorgum. The study was conducted using census methods. The research site determination is intentionally (purposive). The population in this study was the entire sorghum farmers in Wuakerong village amounting to 35 people. The type of data collected was primary and secondary data. The results showed that: (1) The characteristics of farming sorghum in Wuakerong village i.e. sorghum planting is done dry in its own area with an average of 31.57 acres. The use of seed inputs ranges from 0, 125 kg to 0.5 kg depending on the area of the plant. The average production of sorghum obtained by farmer respondents in the 2017 planting season was 245.33 kg/ha. Labor in the sorghum farming is derived from the inside and outside of the family. The average labor use of the family is as much as 5.25 HKO, while the number of family labor used in this farming was 24.0 HKO. The used of outside family labor is not paid because the research village is still using the working system named Gotong Royong so that the cost for labor wage is not calculated, (2) In general, the perception of farmers on sorghum farming is classified as a "very good" category with a percentage of the maximum scoring of the average score of 89.6%. (3) The obstacles faced by sorghum farmers are pest control and difficult to obtain suitable seed and marketing target of sorghum.